Fundamental aspects of long-acting tenofovir alafenamide delivery from subdermal implants for HIV prophylaxis - Gunawardana, Manjula; Remedios-Chan, Mariana; Sanchez, Debbie; Webster, Simon; Castonguay, Amalia E.; Webster, Paul; Buser, Christopher; Moss, John A.; Trinh, MyMy; Beliveau, Martin; Hendrix, Craig W.; Marzinke, Mark A.; et al. (Scientific reports, 2022)
Global efforts aimed at preventing human immunodeficiency virus type one (HIV-1) infection in vulnerable populations appear to be stalling, limiting our ability to control the epidemic. Long-acting, controlled drug administration from subdermal implants holds significant potential by reducing the compliance burden associated with frequent dosing. We, and others, are exploring the development of complementary subdermal implant technologies delivering the potent prodrug, tenofovir alafenamide (TAF). The current report addresses knowledge gaps in the preclinical pharmacology of long-acting, subdermal TAF delivery using several mouse models. Systemic drug disposition during TAF implant dosing was explained by a multi-compartment pharmacokinetic (PK) model. Imaging mass spectrometry was employed to characterize the spatial distribution of TAF and its principal five metabolites in local tissues surrounding the implant. Humanized mouse studies determined the effective TAF dose for preventing vaginal and rectal HIV-1 acquisition. Our results represent an important step in the development of a safe and effective TAF implant for HIV-1 prevention.